2008
DOI: 10.1038/ni.1632
|View full text |Cite
|
Sign up to set email alerts
|

Identification of regulatory functions for 4-1BB and 4-1BBL in myelopoiesis and the development of dendritic cells

Abstract: Abstract4-1BB and 4-1BBL can control adaptive immunity, but we demonstrated that their interaction also suppressed myelopoiesis. 4-1BBL was found to be expressed on hematopoietic stem cells, and differentiating common myeloid (CMPs) and granulocyte-macrophage progenitors (GMPs), and 4-1BB was inducible on activated myeloid progenitors. Steady state numbers of GMPs, myeloidlineage cells, and mature dendritic cells, were elevated in 4-1BB-and 4-1BBL-deficient mice, indicative of a negative functional role, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
100
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 49 publications
(69 reference statements)
8
100
2
Order By: Relevance
“…CD137L protein expressed by LPS-induced TLR4 signaling physically interacts with TLR4, and this interaction is required for LPS-induced sustained TNF production in macrophages [32]. Lee et al, reported that CD137L reverse signals inhibit myelopoiesis and the development of DC [33]. On the other hand, others showed that CD137L ligation enhances proliferation of hematopietic progenitor cells and its differentiation to monocytes, macrophages [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…CD137L protein expressed by LPS-induced TLR4 signaling physically interacts with TLR4, and this interaction is required for LPS-induced sustained TNF production in macrophages [32]. Lee et al, reported that CD137L reverse signals inhibit myelopoiesis and the development of DC [33]. On the other hand, others showed that CD137L ligation enhances proliferation of hematopietic progenitor cells and its differentiation to monocytes, macrophages [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antigen-independent anti-CD137 mAb effects have been described for memory T cells, and CD137 seems to be an important player in the differentiation of memory cells [8][9][10]. CD137 can also be expressed by activated NK cells [11], myeloid leukocytes [12] including DC [13,14], and tumor endothelial cells [15]. However, the role of CD137 molecules expressed on these non-T cells during tumor immunotherapy remains undefined [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…CD137 can also be expressed by activated NK cells [11], myeloid leukocytes [12] including DC [13,14], and tumor endothelial cells [15]. However, the role of CD137 molecules expressed on these non-T cells during tumor immunotherapy remains undefined [13,16].…”
mentioning
confidence: 99%
“…Several TNF family members expressed by APCs can costimulate T cell activation by binding to specific TNFR family members expressed on T cells. 4-1BB (CD137) ligand and OX40 (CD134) ligand, two costimulatory receptors of the TNF family, are expressed on APCs and their ligandreceptor pairs could provide costimulatory signals from APCs to T cells (3). CD27 and CD30 are two additional TNFR family members expressed by T cells that might be interesting targets for the activation or inhibition of antigenspecific responses.…”
Section: Introductionmentioning
confidence: 99%